Pragmatics of Modern German-Language Media Discourse - O. V. Palekhova (Дискурс)
Introduction. The article is devoted to a set of problems related to manipulative influence on the addressee in the mass media, in which the component of information is increasingly aimed at changing public consciousness in order to achieve information superiority and, as a result, to obtain political benefits. The scientific novelty of the research lies in the study of the formation of new background knowledge by appealing to existing stereotypes that affect the perception and interpretation of facts of the surrounding reality. The relevance of this study lies in the growing interest in the problems of speech influence, in the ways and linguistic means of implementing influence.Methodology and sources. The theoretical and methodological basis of the research is formed by linguistic studies of media discourse by T.G. Dobrosklonskaya, G.A. Kopnina; studies of political linguistics, in particular political manipulation, and semiotics of political discourse by E.I. Sheigal, O.V. Mingaleva, O.L. Mikhaleva. The empirical material of the study ist based on political articles of German-language journals for 2020–2024, as well as statistical data of German corpus: DWDS and the German reference corpus DeReKo.Results and discussion. The article describes the main speech techniques and linguistic means of creating and broadcasting stereotypes, through which a picture of the world and, as a result, public opinion is formed in the minds of the mass addressee. The main tactics of speech influence are considered, implying an explicit or implicit assessment of reality in order to influence the emotional and evaluative attitudes of the mass addressee.Conclusion. In political media texts, in particular in German-speaking ones, tactics of speech influence are actively used: opposition, accusation, offense, threat, demonization, as well as manipulative techniques such as omission and/or distortion of information in order to form ideologized stereotypes among the mass addressee and, as a result, influence public consciousness.